The Effect of Storytelling Using Finger Puppets on Anxiety in Hospitalized Preschool Children - Shelfi Dwi Retnani Putri Santoso; Suci Nurjanah (Babali Nursing Research, 2021)
Introduction: The prevalence rates of disease at preschool age are higher than toddlers and school age. The coping mechanism has not developed at that age, thus contributing to increased anxiety levels during hospitalization. Interventions are needed to overcome anxiety problems so that children are more comfortable and cooperative in undergoing treatment in the hospital more effectively. The research aims to examine the effect of storytelling using finger puppets on anxiety in hospitalized preschool children. Methods: Quasi-experiment research with pre and post-test design, 40 preschool children were selected with purposive sampling with inclusion and exclusion criteria, 20 respondents of treatment groups, and 20 respondents of control groups. The instrument used FAS. Data analysis used is the Mann Whitney and Wilcoxon Sign Rank Tests. Results: Mann-Whitney results showed the difference in anxiety between treatment and control group in post-test (p=0.023), and Wilcoxon results showed Z count -3.827 a< Z table -1.96 value asymp sig. (2-tailed) where z arithmetic ≤ z table which means there is influence or probability value p= 0.000 (p< α= 0,05) which means H1 accepted. Conclusion: It is expected that in the future, it can be used as an alternative method to reduce anxiety. And then it’s hoped that researchers can further examine more deeply the effectiveness of parental involvement in storytelling play therapy.